2005
DOI: 10.1007/s10534-005-3718-6
|View full text |Cite
|
Sign up to set email alerts
|

Control of Expression of a Periplasmic Nickel Efflux Pump by Periplasmic Nickel Concentrations

Abstract: There is accumulating evidence that transenvelope efflux pumps of the resistance, nodulation, cell division protein family (RND) are excreting toxic substances from the periplasm across the outer membrane directly to the outside. This would mean that resistance of Gram-negative bacteria to organic toxins and heavy metals is in fact a two-step process: one set of resistance factors control the concentration of a toxic substance in the periplasm, another one that in the cytoplasm. Efficient periplasmic detoxific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 52 publications
3
72
0
3
Order By: Relevance
“…The mechanism and binding partners of the remaining eight RND proteins are as yet undefined (27). Of the four that are each located within a full complement operon, the cobalt-zinc-cadmium resistance proteins (CzcCBA) confer resistance to Cd(II), Zn(II), and Co(II), and the cobalt-nickel-resistance proteins (CnrCBA) confer resistance to Co(II) and Ni(II) (29)(30)(31)(32)(33)(34). zneBAC is also contained in a full complement operon, and we previously showed that the periplasmic MFP ZneB binds to Zn(II) with a K d of ∼3 μM (35), but not to Cd(II) or Co(II) (or other divalent metal ions).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism and binding partners of the remaining eight RND proteins are as yet undefined (27). Of the four that are each located within a full complement operon, the cobalt-zinc-cadmium resistance proteins (CzcCBA) confer resistance to Cd(II), Zn(II), and Co(II), and the cobalt-nickel-resistance proteins (CnrCBA) confer resistance to Co(II) and Ni(II) (29)(30)(31)(32)(33)(34). zneBAC is also contained in a full complement operon, and we previously showed that the periplasmic MFP ZneB binds to Zn(II) with a K d of ∼3 μM (35), but not to Cd(II) or Co(II) (or other divalent metal ions).…”
Section: Resultsmentioning
confidence: 99%
“…For example, iron in tomato apoplastic fluids was measured to be 2.2 to 4.2 M after collection by direct centrifugation (19). At these concentrations of iron, less-well-understood lower-affinity iron import systems are responsible for importing nutritional iron, potentially at a lower energetic cost (21,23). We show that DC3000 could readily utilize a number of different iron sources supplied at these levels (Fig.…”
mentioning
confidence: 78%
“…ZraP is a metal-binding protein that is induced by a two-component system that responds to zinc or lead (33,42), while CnrX is thought to act as a metal sensor that binds cobalt, nickel, and potentially copper in an extracytoplasmic function (ECF)-sigma factor signaling pathway (18,19,34,38,61). Interestingly, copper ions have been implicated as an inducer of the Cpx pathway (26,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%